(untitled) (Journal of Hama University, 2021)
This study aimed at identifying the effectiveness of cognitive therapy with acceptance and commitment in improving self-concept and reducing symptoms of obsessive-compulsive disorder in OCD patients attending the Psychological Division at the Mouwasat Hospital in Damascus. A patient was selected from them to document the treatment steps that were taken according to the qualitative method of the research. In the study, a therapeutic program based on the basic principles of acceptance and commitment therapy was used by the researcher. The Tennessee Scale for self-concept was also used, and the revised mental health scale SCL- 90- R The results showed the effectiveness of acceptance and commitment therapy in OCD patients. The symptoms of disorder decreased and the self-concept improved in the case studied on the scales used in the post application more than in the pre application.